TOUGH CHOICES: Difficulties facing magistrates in applying Protection Orders - Artz, Lillian (SA crime quarterly, 2016)
The second in a series of articles on the Domestic Violence Act considers some of the most difficult issues that magistrates must decide on. These include the temporary removal of the ‘abuser’ from the common home, emergency monetary relief for ‘victims’, and orders specifying the terms of contact with children. Magistrates’ opinions on these controversial issues vary greatly, with the result that victims get uneven assistance from the courts. Magistrates, however, argue that the variation of opinion reflects their independence and discretion, as well as the various capacities of the lower courts to implement the Act.